Analisis Peningkatan Pelayanan Terminal Penumpang Nusantara Di Pelabuhan Tanjung Priok - Raga, Paulus; Estherina, Lieswati; Salsabila, Novia Putri (Jurnal Sistem Transportasi & Logistik, 2023)
Ports have the role of being a meeting point between transportation and interests in it which include services to ships, passengers, and cargo. In order to strive for the best service, it is necessary to evaluate passenger services at the port. In evaluating the level of passenger service at the Nusantara Pura II Tanjung Priok passenger ship terminal, using the Importance Performance Analysis (IPA) method, it was found that there was an increase in service and service performance flow for passenger ship facilities at the Tanjung Priok port terminal on 15 facility attributes, and resulted in customer satisfaction scores. to service facilities, namely "SATISFACTORY".